Perceived Seriousness Of Wrongdoing And Peer Reporting Intention: The Moderating Role Of Wrongdoer’s Status - Andrey Hasiholan Pulungan; Audrey Azzahra; Kenny Fernando; Budi Kurniawan (Universitas Pendidikan Indonesia, 2023)
Main Purpose - This study intends to evaluate the moderating effect of wrongdoer status (close friends or acquaintances) on the link between perceived wrongdoing seriousness and intention to report academic misconductMethod - This research used a 1x2 experimental design between subjects. One hundred eleven participants from three universities were involved in the experiments. Participants were selected using a method of purposive sampling. However, only 106 responses can be analyzed using SMART PLS 4 due to insufficient responses from some participants.Main Findings - The findings indicate that students are more likely to report academic misconduct when they consider it to be more severe. However, if the perpetrator is a close friend, the likelihood of a student reporting academic misconduct is significantly reduced.Theory and Practical Implications – This study has consequences for how colleges respond when students report their friends for academic dishonesty. Students fear that if they report the inappropriate activity of their close friends, they would be left by their friends. Educating students and faculty members on the need of recognizing and reporting academic dishonesty could contribute to the creation of an ethical university culture.Novelty – Prior research has often been descriptive and qualitative, meanwhile, this study applies path analysis to provide empirical evidence specifically in the Indonesian context about the impact of friendship on students' willingness to report academic misconduct.